2004
DOI: 10.1021/ja046757y
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Solute Nucleophilicity with Room Temperature Ionic Liquids

Abstract: In this work we report the effect of ionic liquids on a class of charge-neutral nucleophiles. We have studied the reactions of (n)butylamine, di-(n)butylamine, and tri-(n)butylamine with methyl p-nitrobenzenesulfonate in [bmpy][N(Tf)(2)], [bmpy][OTf], and [bmim][OTf] (bmpy = 1-butyl-1-methylpyrrolidinium; bmim = 1-butyl-3-methylimidazolium) and compared their reactivities, k(2), to those for the same reactions in the molecular solvents dichloromethane and acetonitrile. It was shown that all of the amines are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(202 citation statements)
references
References 40 publications
11
188
3
Order By: Relevance
“…Indeed, according to previous reports, 19 among aromatic protons of imidazolium ion, the H2 proton is the one able to give the strongest interaction with the anion and, consequently, it is the most affected by amine presence. A similar amine structure effect was previously found by Welton et al 20 and subsequently confirmed by us. 21 On the other hand, this interaction allows us to rationalize the lowest influence of the amine presence on the aliphatic protons of imidazolium ion, not interacting, with the IL anion.…”
Section: Issn 1551-7012supporting
confidence: 91%
“…Indeed, according to previous reports, 19 among aromatic protons of imidazolium ion, the H2 proton is the one able to give the strongest interaction with the anion and, consequently, it is the most affected by amine presence. A similar amine structure effect was previously found by Welton et al 20 and subsequently confirmed by us. 21 On the other hand, this interaction allows us to rationalize the lowest influence of the amine presence on the aliphatic protons of imidazolium ion, not interacting, with the IL anion.…”
Section: Issn 1551-7012supporting
confidence: 91%
“…A high yield of an organic reaction can be obtained by the choice of a suitable ionic liquid or a binary mixture of two or more ionic liquids, see e.g., Refs. [29][30][31]. RTILs have been used as solvent media for organic synthesis and new types of catalysts, lubricants, carbon-nano tubes, etc.…”
Section: N]mentioning
confidence: 99%
“…The intense scientific interest in RTILs stems from their complex combination of interactions, van der Waals, Coulomb, dipole, and hydrogen bonding, rarely occurring simultaneously in other materials [5,6]. Being infiniteconcentration ionic "solutions", RTILs are strongly correlated systems, going beyond the validity regime of the Poisson-Boltzman equation, and the Gouy-Chapman and Stern models of the electric double layer [7], and thus allowing insight into this scarcely studied regime.…”
mentioning
confidence: 99%